2021
DOI: 10.2147/jep.s267378
|View full text |Cite
|
Sign up to set email alerts
|

Review on Experimental Treatment Strategies Against Trypanosoma cruzi

Abstract: Chagas disease is a neglected tropical disease caused by the protozoan Trypanosoma cruzi . Currently, only nitroheterocyclic nifurtimox (NFX) and benznidazole (BNZ) are available for the treatment of Chagas disease, with limitations such as variable efficacy, long treatment regimens and toxicity. Different strategies have been used to discover new active molecules for the treatment of Chagas disease. Target-based and phenotypic screening led to thousands of compounds with anti- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 217 publications
(430 reference statements)
0
42
0
Order By: Relevance
“… 40 However, no novel chemical entity has yet been discovered or implemented for this silent disease although some pre-clinical studies have reported promising drug candidates for CD, including nucleoside derivatives that act on the purine salvage pathway. 41 Our group reassessed the natural antibiotic tubercidin and a series of 7-substituted analogues aiming to identify novel hits against Trypanosoma brucei , the agent of human African trypanosomiasis. 42 Besides being very active against T. brucei , some phenyl-substituted analogues also presented high in vitro potency against T. cruzi , which motivated us to explore related 7-substituted 7-deazapurine moieties with the carbohydrate group of cordycepin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“… 40 However, no novel chemical entity has yet been discovered or implemented for this silent disease although some pre-clinical studies have reported promising drug candidates for CD, including nucleoside derivatives that act on the purine salvage pathway. 41 Our group reassessed the natural antibiotic tubercidin and a series of 7-substituted analogues aiming to identify novel hits against Trypanosoma brucei , the agent of human African trypanosomiasis. 42 Besides being very active against T. brucei , some phenyl-substituted analogues also presented high in vitro potency against T. cruzi , which motivated us to explore related 7-substituted 7-deazapurine moieties with the carbohydrate group of cordycepin (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy of repurposing drugs has been used as a fast alternative for different neglected diseases [ 4 , 23 , 46 ]. Previous data has shown a high TMX in vitro activity (IC 50 2.4 µM) against amastigotes and promastigotes of Leishmania and in vivo efficacy at doses of 20 mg/kg in infected-mice and hamsters [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the efforts to discover novel and safe drugs, anti- T. cruzi chemotherapy for both newborns and adults still relies on nifurtimox (NFX) and benznidazole (BZN), two drugs discovered in the '60s with known adverse side effects ( 64 , 66 ). To improve CD treatment, strategies based on combinations of existing drugs or re-dosing regimens are currently being evaluated ( 67 ). Even though the excellent efficacy in reducing the parasitaemia when administered during the acute phase, CD treatment is less effective in preventing the clinical progression when given long time after the initial infection, suggesting a role for the host immune response ( 68 ).…”
Section: Chagas Diseasementioning
confidence: 99%